Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Sphingobacterium endophyticum sp. nov., a novel endophyte isolated from halophyte - Yang-Yang Liu; Fang Liu; Yu-Qian Li; Rui-Feng Lei; Qin Ma; Manik Prabhu Narsing Rao; Dilireba Abudourousuli; Zulihumaer Rouzi; Muyesaier Aosiman; Deng-Di An; Wen-Jun Li (Archives of Microbiology, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

MELK Accelerates the Progression of Colorectal Cancer via Activating the FAK/Src Pathway - Guangming Liu; Wei Zhan; Wei Guo; Feng Hu; Junjie Qin; Rui Li; Xin Liao (Biochemical Genetics, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Cloning and expression of Allophycocyanin gene from Gracilariopsis lemaneiformis and studying the binding sites of phycocyanobilin on its α and β subunits - Yalin Guo; Xiaonan Zang; Xuexue Cao; Feng Zhang; Deguang Sun; Menghui Shang; Rui Li; Zhaxi Yangzong; Xuehong Wei; Xuecheng Zhang (Journal of Applied Phycology, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Moderate parasitoidism on pollinators contributes to population oscillations and increases species diversity in the fig-fig wasp community - Lin Wang; Li-Yuan Yang; Feng Zhang; Rui-Wu Wang (Theoretical Ecology, 2020)

Rapid and efficient removal of naproxen from water by CuFe2O4 with peroxymonosulfate - Rui Bai; Yong Xiao; Weifu Yan; Siqi Wang; Rui Ding; Fan Yang; Junpeng Li; Xiaoquan Lu; Feng Zhao (Environmental Science and Pollution Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

First report of broad bean wilt virus 2 infection in eggplant in China - Peng-Huan Rui; Lei Jiang; Shuai Li; Xi-Zi Jiang; Qing-Qing Zhao; Ji Ying Feng; Tong Jiang (Journal of Plant Pathology, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Quantitative proteomic analysis reveals that the Rap1/MAPK/ERK pathway is inhibited through selenomethionine strengthening antioxidant activity - Zhe Liu; Feng Zhang; Lina Cui; Jihong Wang; Ping Lu; Rui Zhao; Hua Zhang; Jianfa Wang; Chunqiu Li; Rui Wu (BioMetals, 2020)

PDGFRβ-targeted TRAIL specifically induces apoptosis of activated hepatic stellate cells and ameliorates liver fibrosis - Rui Li; Zhao Li; Yanru Feng; Hao Yang; Qiuxiao Shi; Ze Tao; Jingqiu Cheng; Xiaofeng Lu (Apoptosis, 2020)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)